The Relationship between Exchange Rate and Inflation: An Empirical Study of Turkey - Abdurehman, Abderezak Ali; Hacilar, Samet (International Journal of Economics and Financial Issues, 2016)
This paper investigates the relationship between inflation and exchange rate in Turkey. Unlike many empirical studies which make use of the US and Turkey inflation data to test the relationship between inflation and exchange rate in Turkey, this paper employed inflation data of Turkey and the United Kingdom. An OLS regression and a simple GARCH model were used to understand the relationship between inflation and exchange rate. The results obtained from OLS regression indicate Purchasing Power Parity (PPP) does not exist in Turkey. However, the existence of ARCH and GARCH in the relationship indicates that the deviations from PPP are not random and follow a certain pattern. Therefore, we conclude that the deviation of PPP might be attributed to certain factors such as transaction cost, government restriction, product specialization or other related factors. Keywords: Exchange Rate, Inflation, GARCH model JEL Classifications: C87; E31; F31